2012
DOI: 10.1063/1.3673830
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly of C60 monolayer on epitaxially grown, nanostructured graphene on Ru(0001) surface

Abstract: C60 molecules adsorbed on graphene/Ru(0001) substrate were investigated by scanning tunneling microscopy (STM) at 5 K. On high quality substrates, C60 molecules adopt a commensurate growth mode, leading to formation of a supramolecular structure with perfect periodicity and few defects. On under-annealed substrates with imperfections and domains, the molecules form the same closely packed hexagonal structures in spite of underlying corrugations, disorders or steps, indicating a weak molecule-substrate interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 30 publications
4
32
1
Order By: Relevance
“…Recently, two studies of C 60 molecules on graphene on Ru(0001)120 and on SiC(0001)121 were conducted in order to examine the molecule‐surface interaction in graphene‐based, organic photovoltaics. In the case of C 60 on graphene/Ru(0001), the C 60 molecules pack in a commensurate manner to form a supramolecular structure with a perfect and continuous periodicity with few defects.…”
Section: Processing and Modificationmentioning
confidence: 99%
“…Recently, two studies of C 60 molecules on graphene on Ru(0001)120 and on SiC(0001)121 were conducted in order to examine the molecule‐surface interaction in graphene‐based, organic photovoltaics. In the case of C 60 on graphene/Ru(0001), the C 60 molecules pack in a commensurate manner to form a supramolecular structure with a perfect and continuous periodicity with few defects.…”
Section: Processing and Modificationmentioning
confidence: 99%
“…C 60 adsorbed on surfaces generally tend to form hexagonal close-packed arrangements 11 in order to optimize their lateral interactions. In very recent studies of C 60 molecules deposited on SLG epitaxially grown on metal, 12,13 it has been shown that the interaction between the molecules and the substrate, and consequently the molecular arrangement, is ruled by the moiré unit cell. The C 60 coming to the surface are trapped in potential wells of the moiré valleys where the substrate SLG is more reactive, thus forming pinning centers for the other molecules that arrange in between.…”
mentioning
confidence: 99%
“…Organic molecules adsorbed on epitaxially grown graphene on metal substrates have also been investigated by STM to explore the possibility of graphene based organic devices [18][19][20][21]. According to the occurrence of intrinsic molecular electronic states on graphene for molecules such as perrylene, pentacene and fullerene [20], graphene appears to act as a buffer layer to reduce the interaction between molecules and metal substrates.…”
Section: Introductionmentioning
confidence: 99%